A Rare Case of a Migrating Inguinal Hernia Mesh Presenting as Acute Appendicitis - Jorge Nogueiro; Hugo Santos-Sousa; Marinho de Almeida; Luis Malheiro; Elisabete Barbosa (Case Reports in Surgery)
Acute appendicitis is a very common event. Migration of hernia mesh is rare, especially intraluminal migrations. We aim to report a case of a migrated inguinal mesh presenting as an acute appendicitis. A 58-year-old male previously submitted to ONSTEP right inguinal hernia repair with a PolySoft™ hernia patch eight years before, was admitted in the emergency department with acute appendicitis, and submitted to laparoscopic appendectomy. Intraoperatively, the “recoil ring” from the inguinal hernia patch was extended from the anterior abdominal wall to the appendix, perforating it and progressing intraluminally. Appendectomy was performed, as well as removal of the mesh by an anterior approach. Hernia mesh migration to an intraluminally position is extremely rare with only a few cases described in literature. Pathogenesis of migration is still poorly understood. Clinicians should consider hernia mesh migration in their differential diagnosis for causes of acute appendicitis, in the right clinical setting, when a previous hernia defect correction is present. To the best of our knowledge, this is the first reported case of inguinal hernia mesh migration to the appendix, presenting as acute appendicitis.